Primer Congreso Nacional de Información para el Desarrollo: “Costa Rica hacia la sociedad de la información de todos para todos” : Informe final mesas de trabajo - Gil Calderón, Marcela (2013)
It presents the final report of the working groups of the First National Congress on Information for Development "Costa Rica to the information society for all" held on September 29-30 and October 1, 2010, at the University of Costa Rica, San Pedro de Montes de Oca, Costa Rica and organized by the School of Library Science at the University of Costa Rica.